Pengaruh Projek Penguatan Profil Pelajar Pancasila (P5) Terhadap Minat Belajar Siswa Kelas X Pada Mata Pelajaran Biologi Di SMA Negeri 1 X Koto Singkarak - Dela Navarin; Irwan Hanafi; Chairul Amri (CV. ITTC INDONESIA, 2026)
Based on observations at SMA Negeri 1 X Koto Singkarak, it can be seen that there are still some students who lack interest in learning, as seen in some classes, students are busy with their own activities in the learning process, lack of student participation in the learning process and students' attitude is not enthusiastic in the learning process. The purposeis to find out the Influence of the Pancasila Student Profile Strengthening Project (P5) on the Learning Interest of Class X Students in Biology Subjects at SMA Negeri 1 X Koto Singkarak. Descriptive quantitative research was used. This study involved class X students at SMA Negeri 1 X Koto Singkarak, and the sample amounted to 70 students. The samplingtechnique used is the Slovin formula. Data was collected through questionnaires, and data analysis was carried out by simple linear regression analysis. Before conducting regression analysis, the researcher conducted a descriptive statistical analysis and a prerequisite test, namely a normality test, using the Smirnov Kolmogrov Test and a linearity test, using theSPSS version 22 program. Then a simple linear regression test was performed. Furthermore, the passive test (t-test) and the determination coefficient test were used to test the hypothesis. The results of the hypothesis test conducted using the 22-windows version of SPSS were found with a tcal value of 2.063 greater than the ttable of 1.667, indicating that H0 was rejected and Ha was accepted, indicating that the proposed hypothesis was accepted. This means that there is a significant relationship between the project to improve the profile of Pancasila students and their interest in learning.